2023
DOI: 10.1037/xhp0001148
|View full text |Cite
|
Sign up to set email alerts
|

Competition and reward structures nearly eliminate time-on-task performance decrements: Implications for theories of vigilance and mental effort.

Abstract: Across four experiments, we manipulated features of a simple reaction time (RT) task to examine the effects of such features on sustained attention. In Experiment 1, we created simple RT "game" that pitted participants against two computerized avatars. In one condition, participants were awarded points, while the other condition did not receive points. Performance in the two conditions did not differ, but both conditions showed shorter RTs and shallower time-on-task performance decrements compared to a standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…In comparison, Luna et al (2022) found a greater vigilance decrement in individuals who experienced greater declines in executive control with time on task. These, and other findings (e.g., Robison and Nguyen, 2023), indicate both cognitive and emotional elements may underlie vigilance, which may relate to cardiac vagal tone (Laborde et al, 2017;Forte et al, 2019). Given that HRV can index cardiac vagal tone, which is associated with the neural substrates that regulate cognitive and emotional resources, both of which are proposed to be essential elements of vigilance, it stands to reason that cardiac vagal tone should correlate with vigilance performance.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…In comparison, Luna et al (2022) found a greater vigilance decrement in individuals who experienced greater declines in executive control with time on task. These, and other findings (e.g., Robison and Nguyen, 2023), indicate both cognitive and emotional elements may underlie vigilance, which may relate to cardiac vagal tone (Laborde et al, 2017;Forte et al, 2019). Given that HRV can index cardiac vagal tone, which is associated with the neural substrates that regulate cognitive and emotional resources, both of which are proposed to be essential elements of vigilance, it stands to reason that cardiac vagal tone should correlate with vigilance performance.…”
Section: Introductionmentioning
confidence: 78%
“…It should be noted that a myriad of additional variables underlie individual differences in cardiac vagal tone (e.g., age, sex assigned at birth, physical fitness, genetics, to name a few; Umetani et al, 1998 ; De Meersman and Stein, 2007 ) as well as vigilance performance (e.g., gender, personality, ability, participant engagement, motivation, coping skills, etc. ; Eysenck, 1989 ; Rose et al, 2002 ; Matthews et al, 2010 , 2017 ; Shaw et al, 2010 ; Neigel et al, 2017 , 2018 ; Peltier and Becker, 2017 ; Claypoole et al, 2018 ; Teo et al, 2018 ; Rice and Greenlee, 2019 ; Robison and Nguyen, 2023 ). Given the exploratory nature of this investigation, we do not further explore these factors nor do we have a priori hypotheses on how cardiac vagal tone will trend during a vigilance task, before and after a break, for different magnitudes of the vigilance decrement and/or for different task loads, and if (and how) this all depends on the individual.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative theories conceptualize cognitive effort as the solution to a computational problem. In particular, the opportunity cost hypothesis holds that cognitive effort occurs when the reward value of the current task under execution is less than the potential reward value of an alternative task, thereby promoting a shift to the other task (Agrawal et al, 2022; Boureau et al, 2015; Inzlicht et al, 2014; Kurzban et al, 2013; Robison & Nguyen, 2023; Thorndike, 1899). Cognitive effort could also induce pauses in cognitive activity that allow new memories to be consolidated in cortex (Agrawal et al, 2022; Holroyd & Verguts, 2021), consistent with computational arguments (Roscow et al, 2021) and biological (Holroyd & Verguts, 2021) and behavioral (Gershman et al, 2014; Wamsley, 2022) evidence of this.…”
mentioning
confidence: 99%
“…These findings are encouraging as they provide a potential avenue by which to intervene and possibly reduce occurrences of mind wandering during a cognitive assessment. For example, a simple manipulation designed to increase participant motivation led to reduced rates of mind wandering and a concomitant improvement in task performance (Seli et al, 2019; Smith et al, 2022) or reduction in the vigilance decrement (Robison & Nguyen, 2023). To the extent that other dispositional factors, such as mood and Conscientiousness, influence mind wandering, additional interventions (e.g., to improve participant mood or increase levels of Conscientiousness) could also be considered.…”
mentioning
confidence: 99%